Project-based learning: A scope review to support the teaching process in higher education - Canto, Cleunisse Aparecida Rauen de Luca; Silveira, Maristela Schleicher; Piana, Valério Junior; Endres, Creciana Maria (Seven Editora, 2023)
Motivating and preparing students for the changes that the world of work imposes is challenging and requires a renewal in the teaching and learning process. In order for education to fulfill its social and formative role, educational approaches should provide students with experience in real problems. In this sense, Project-Based Learning (PBL) is a suitable proposal for the didactic-pedagogical process of universities. The objective of this study is to analyze scientific publications in recent years on the application of PBL in higher education. For this purpose, a descriptive exploratory research was carried out, based on a scoping review. 355 works were identified in the literature, which after applying eligibility criteria resulted in 52 articles (14.6%), and after analyzing the complete article, 14 (27%) remained and served as a support to substantiate the present work. The analysis allowed us to observe that PBL provides students with a direct relationship with real challenges in the industry, finding solutions and treatments for identified problems, which allows the development of competencies based on applied knowledge. DOI:https://doi.org/10.56238/ptoketheeducati-040